PENGARUH MODEL CONCEPT SENTENCE DENGAN MEDIA FLASH CARD TERHADAP KEMAMPUAN MENULIS DI SDN SANDANA - Fitriani Djafar; Hamna; Moh. Rudini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the concept sentence learning model assisted by flash card media on the narrative writing skills of fourth-grade students at SDN Sandana. The background of this research is the low ability of students in writing narratives, as indicated by difficulties in arranging paragraphs according to structure, the use of colloquial language, and the limited use of appropriate conjunctions. This research employed a quantitative approach with a Quasi-Experimental Nonequivalent Control Group design. The sample consisted of 32 students, divided into an experimental class (using the concept sentence model with flash card media) and a control class (conventional learning). Data were collected through observation, writing tests (pretest and posttest), documentation, and student response questionnaires. Data analysis used the Shapiro-Wilk test, Wilcoxon Signed Rank Test, and N-Gain Score calculation. The results showed a significant improvement in the writing ability of the experimental class, with the average score increasing from 39.06 to 82.19 (an increase of 43.13 points), while the control class only increased from 27.5 to 34.38 (an increase of 6.88 points). Student responses to the learning process were also highly positive. It is concluded that the concept sentence learning model assisted by flash card media is effective and significantly improves the narrative writing skills of elementary school students. Keywords: Sentence Concept Model, Flash Card Media, and Writing Skills